Aplikasi Membran Filter Keramik Untuk Menurunkan Konsentrasi Zat Warna Remazol Red dan Nilai COD Limbah Cair Batik - Nur Fitriana; Maya Rahmayanti (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2020)
Research on the application of ceramic filter membranes in reducing remazol red dye concentration and COD value of batik liquid waste has been carried out. The purpose of this study was to reduce the remazol red dye concentration and the COD value of batik wastewater using a ceramic filter membrane. The ceramic filter membrane used was made from clay and silica sand with variations in the number of additions of wood sawdust as much as 0, 1, 3, 5 and 7%. Then the porosity of the ceramic filter membrane was tested to determine the percentage of the pore volume that the ceramic filter membrane had. The ceramic filter membrane with the composition of clay, silica sand and 1% wood sawdust was the most optimum in reducing remazol red dye up to 86.68% and reducing COD value up to 97.87%. Keywords: filtration, remazol red, COD, ceramic filter membranes, batik liquid waste